Perancangan Keselamatan dan Kesehatan Kerja (K3) pada peternakan ayam broiler Alif di Desa Jatiroto dengan metode HIRARC - Larasati, Shafira Hanifa; Hidayah, Muhammad Nur Wahyu; Widyastuti, Widyastuti; Nursanti, Ida Beta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational Health and Safety (OHS) in broiler chicken farms is very important to prevent work accidents and diseases. This study used the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method to identify potential hazards and assess their risks. Data were obtained through direct observation and interviews at the Alif Broiler Chicken Farm. The results showed that there were 16 potential hazards, with 10 categorized as low risk and 6 as medium risk. The main hazards include injuries due to chicken pecking, irritation from disinfectants, and muscle injuries due to lifting heavy loads. This study also identified the absence of standard operating procedures (SOPs) as one of the main causes of work accidents. To reduce the risk, the use of personal protective equipment (PPE) and strict implementation of SOPs are recommended. In conclusion, preventive hazard control through SOPs can improve work safety in broiler chicken farms.